Effect Of A Variety Exercises On Some Physical Abilities And Shooting Accuracy Of Free Kick For Junior Football Players - et. al, Asst. Lec. Firas Bayyat Mohammad , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of the research lies in preparing a variety of exercises and knowing their effect on some physical abilities and the accuracy of the scoring skill for the direct free kick in football for young players. As for the research problem: the researchers believe that the research problem is concentrated in the lack of coaches' use of various exercises to develop the physical abilities that are directly involved in the performance of the direct free kick in football. Therefore, the researchers considered preparing a variety of exercises (physical and skill), which would affect some physical abilities that contribute to the accuracy of direct free kick soccer scoring, so the researchers wanted to delve into this experiment. The research aimed to: Preparing a variety of soccer exercises and knowing the effect of various exercises on some physical abilities contributing to the accuracy of direct free kick scoring for young football players. As for the search hypothesis: There is an effect of various exercises on some physical abilities of young football players and there is an effect of various exercises on the accuracy of direct free kick scoring for young football players. As for the research methodology and field procedures, the researchers used the experimental method to solve the research problem , as for the research community, it has been identified with the junior players of the Baghdad governorate clubs for the season 2020-2021, and their number is (8) players who are proficient in the direct free kick skill, and they were distributed into two groups (experimental and control) by simple random method (lottery). As for the most important conclusions, they were as follows: The various exercises helped to develop some physical abilities represented by (explosive ability, speed characteristic, motor speed), and the various exercises contributed to developing the accuracy of direct free kick soccer scoring. While the most important recommendations included the following: The researchers recommend paying attention to the use of various exercises according to scientific methods and training methods when training football players, and the researchers recommend conducting similar studies on different age groups.